TCDD-Inducible Poly-ADP-Ribose Polymerase (TIPARP), A Novel Therapeutic Target Of Breast Cancer - Cheng L; Li Z; Huang YZ; Zhang X; Dai XY; Shi L; Xi PW; Wei JF; Ding Q (Cancer Management and Research, 2019)
Lin Cheng,1,2,* Zhi Li,1,* Yu-Zhou Huang,1,* Xu Zhang,1 Xin-Yuan Dai,1 Liang Shi,1 Pei-Wen Xi,1 Ji-Fu Wei,3 Qiang Ding1 1Jiangsu Breast Disease Center, The First Affiliated Hospital with Nanjing Medical University, Nanjing 210029, People’s Republic of China; 2Department of Breast Surgery, The Affiliated Changzhou No. 2 People’s Hospital of Nanjing Medical University, Changzhou 213003, People’s Republic of China; 3Research Division of Clinical Pharmacology, The First Affiliated Hospital with Nanjing Medical University, Nanjing 210029, People’s Republic of China*These authors contributed equally to this workCorrespondence: Qiang DingJiangsu Breast Disease Center, The First Affiliated Hospital with Nanjing Medical University, 300 Guangzhou Road, Nanjing 210029, People’s Republic of ChinaTel +86-25-83673123Email dingqiang@njmu.edu.cnJi-Fu WeiResearch Division of Clinical Pharmacology, The First Affiliated Hospital with Nanjing Medical University, 300 Guangzhou Road, Nanjing 210029, People’s Republic of China, Tel +86-25-68306984Email weijifu@hotmail.comBackground: TIPARP (TCDD-inducible poly-ADP-ribose polymerase), a mono-ADP-ribosyltransferase and a transcriptional repressor of aryl hydrocarbon receptor (AHR), was one of the potential therapeutic targets for human cancers identified by CRISPR–Cas9 screens recently. Studies about TIPARP on cancers are scarce till now, most of which just focus on expressions, while the functions have not been widely reported yet. Moreover, the TIPARP prognostic significance and therapeutic value of breast cancer is also uncertain.Methods: The present study was performed to comprehensively analyze the expression pattern, prognostic effect, potential therapeutic function of TIPARP in breast cancer by pooling all currently available databases online including Oncomine, UALCAN, bc-GenExMiner, Kaplan–Meier Plotter, COSMIC, UCSC Xena, STRING, DAVID and Comparative Toxicogenomics Database. Further, we also performed several cell biology experiments including RT-qPCR, Western blot and CCK-8 in cellular and clinical sample levels to confirm the conclusions from bioinformatics analysis.Results: TIPARP was expressed lower in tumor tissues comparing with normal tissues. Meanwhile, several clinical parameters of breast cancer patients were correlated with TIPARP expression. Further, higher TIPARP expression was related to preferable survival. Moreover, the mutations and DNA methylation of TIPARP might contribute to TIPARP dysregulation in breast cancer. Interactors with TIPARP were signiﬁcantly enriched in telomere maintenance, telomere organization and mainly participated in pathways in cancer. Finally, several common drugs including metformin were observed to up-regulate the expression of TIPARP.Conclusion: TIPARP might act as a preferable prognostic marker of breast cancer through multiple biological processes such as DNA methylation, mutation as well as pathway related to telomere and so on. TIPARP could be considered as a potential therapeutic target for breast cancer. However, large-scale and comprehensive research is needed to clarify our results.Keywords: TIPARP, breast cancer, therapeutic target